Intimate media: new queer documentary and the sensory turn. Issue 3 (1st September 2020) - Geiger, Jeffrey
ABSTRACT: The heightened visibility of LGBTQ documentaries is often viewed within critical contexts of New Queer Cinema: B. Ruby Rich's intervention which highlighted an urgency among a new kind of practice, identifying trends across queer film and video. This article explores contours of new queer documentary which played an important role in New Queer Cinema, re-examining ways that queer nonfiction film and video evolved out of distinctive relations to the history and traditions of the documentary form, its established practices, and commonly-held social functions. This approach underlines ways that this work's often intense evocations of sexuality and bodily sentience as experienced across private and public space marked a crucial moment in what David Howes calls a transdisciplinary sensorial revolution. Keeping mobile and productive cross-pollinations of practice and theory in frame, this article explores emerging vocabularies for the cinematic experience by distilling components, here summed up as intimacy, gesture, and magnitude, of new queer documentary that operated not in opposition to but as part of a transvaluation of documentary's long-established associations. With a focus on the fraught politics of new queer documentary in US contexts, these concepts are analysed through key filmmakers, including Barbara Hammer, Tom Joslin, and Marlon Riggs.